THE EFFECT OF CLASSICAL MUSIC THERAPY ON ANXIETY OF CANCER PATIENTS UNDERGOING CHEMOTHERAPY IN A PRIVATE HOSPITAL, BEKASI CITY: THE EFFECT OF CLASSICAL MUSIC THERAPY ON ANXIETY OF CANCER PATIENTS UNDERGOING CHEMOTHERAPY IN A PRIVATE HOSPITAL, BEKASI CITY - Ery Natalina Kristianingsih, Yosefhine; Rohayati, Rohayati (Jurnal Mitra Kesehatan, 2024)
Introduction : Cancer is a non-communicable disease with a high incidence and mortality rate in Indonesia and the world. The most common cancer treatment is chemotherapy. Chemotherapy often causes psychological effects, such as anxiety. This study aims to determine the effectiveness of classical music therapy on anxiety in cancer patients with chemotherapy at a Private Hospital , Bekasi City. Method: The design of this study was a quasi-experiment with a one-group pre- and post-test without a control group, involving 33 cancer patients according to the inclusion criteria, namely cancer patients with chemotherapy, experiencing anxiety, not experiencing hearing loss, over 17 years of age, and not using anti-anxiety therapy. This study has passed the ethics number EC. 062 / KEPK / STKBS / IV / 2022. Result: The results of the study showed that there was an effect of classical music therapy on reducing anxiety in cancer patients undergoing chemotherapy, with a p value of 0.000.. Conclusion: The study's results indicate that classical music therapy effectively lowers anxiety levels in cancer patients undergoing chemotherapy.